Інтеграція квантових обчислень в експертні системи з нечіткою логікою - Безверхий, Анатолій Ігорович; Скрипник, Ірина Анатоліївна; Жуков, Олександр Олексійович; Bezverkhyi, Anatoliy; Skrypnyk, Iryna; Zhukov, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: В роботі представлено концептуальну архітектуру та програмну реалізацію інтелектуальної системи, що об’єднує три парадигми: нечітку логіку, експертні системи та квантові алгоритми. За допомогою інструментарію scikit-fuzzy на мові Python реалізовано експертну систему з нечіткою логікою. Вона обробляє неточні вхідні дані і генерує тривалість поливу. Для вибору оптимальної стратегії в умовах невизначеності використовується симуляція квантового алгоритму за допомогою бібліотеки Qiskit від IBM. Інтеграція зазначених підходів дозволяє створити систему прийняття рішень, де нечітка логіка забезпечує гнучкість, експертна система – надійність, а квантові обчислення – оптимізацію стратегії. Представлений приклад демонструє можливості побудови гібридних систем для вирішення багатофакторних завдань у таких галузях, як точне землеробство, автоматизація виробничих процесів та управління ресурсами. /// EN: This paper presents the conceptual architecture and software implementation of a hybrid intelligent system that synthesizes three fundamental computing paradigms: fuzzy logic, expert systems, and quantum algorithms. The objective of this work is to demonstrate the synergistic effect of their combination in solving an applied problem – optimizing plant irrigation based on an analysis of external conditions. A fuzzy logic system is implemented in Python using the scikit-fuzzy toolkit. It processes imprecise input data (soil moisture, air temperature) and generates a baseline quantitative assessment – the irrigation duration – based on a set of linguistic rules. Based on the output from the fuzzy inference layer, a system of higher-order rules (an expert system) is applied. This layer introduces deterministic adjustments based on additional, contextual knowledge, thereby enhancing the reliability and adequacy of the final decision. To select the optimal course of action under conditions of uncertainty, a quantum algorithm simulation is employed using IBM’s Qiskit library. This allows for the final optimization of the recommended duration. Conclusions. The integration of the approaches described in this paper allows for the creation of a multi-level decision-making system where each technology performs a unique function: fuzzy logic provides flexibility, the expert system ensures reliability and control, and quantum computing delivers strategy optimization. The presented case study illustrates the potential of hybrid systems for solving complex, multi-factor problems in domains such as precision agriculture, industrial process automation, and resource management.
Integrating quantum computing into fuzzy logic expert systems
Keywords: гібридна інтелектуальна система; нечітка логіка; експертна система; квантові обчислення; оптимізація; hybrid intelligent system; fuzzy logic; expert system; quantum computing; optimization